PENGEMBANGAN MASYARAKAT MARITIM DI TEMPAT PELELANGAN IKAN (TPI) DI PULAU TOMIA - Nurul Hidayah Asraruddin; Lista Patiung (Riset Sains dan Teknologi Kelautan, 2023)
Wakatobi is one of the districts located in the southeast of Sulawesi island. Wakatobi has four major islands including Wangi-Wangi, Kaledupa, Tomia and Binongko. The islands are separated by the ocean. Therefore, this country has considerable potential for marine resources. One of them is related to aquatic resources. For this reason, it is necessary to have a separate location to increase the development of fish stocks in that location, for example with a Fish Auction Place (TPI). Fish Auction Place (TPI) is a place for buying and selling fish and marine products, whether in the form of auction or not, which is located in a port or Fishery Pier (PPI). One of them is located on Tomia Island. The TPI, which was inaugurated in 2018, is expected to increase local revenue (PAD) [1], but in its development it encounters a number of internal and external constraints that can still be overcome through increased development of TPI resources. The purpose of this research is to analyze the development strategy of maritime community in Fish Sales Place (TPI). This research uses descriptive method. With more than 17,000 islands and a coastline length of approximately 81,000 km, Indonesia's coast is an important part of the country's economy. Coastal areas are usually defined as places where all ecosystems meet in a delicate balance. The area of Wakatobi Regency is surrounded by sea water, namely, Buton, Banda, and Flores [3]. Tomia Island has a diversity of economic potential from its tourism and natural resources due to its strategic location. Most of the population works as fishermen, which causes the economic condition of the region to be unstable because the main income comes from the sea.   Keywords : Fish, Sea, Island, Tomia, TPI